Diabetes-associated biobanking: more topical than ever? - Kynast, Katharina; Volk, Nadine; Fleming, Thomas; Herpel, Esther (Experimental and clinical endocrinology & diabetes, 2017)
The increasing prevalence of diabetes and its accompanying long-term complications, as well as the associated economic burden, calls for a rapid clinical translation of biomedical research to better valid the physiological relevance of the findings from basic research. To meet this condition, the Collaborative Research Center (CRC) 1118 has established the first nationwide diabetes-specific Biomaterialbank (BMB) that permanently preserves solid and liquid specimen retro- and prospectively at the Institute of Pathology and Department of Endocrinology of the University Hospital Heidelberg. The main purpose of this BMB is to collect, preserve, characterize and provide human diabetic specimen to researchers investigating the role of reactive metabolites (RM) as cause of diabetic late complications. In this review we discuss the urgent need to support translational and clinical research projects by making use of diabetic solid and liquid specimen and provide an insight into the organization and general conditions of biobanking procedures which are pivotal to guaranteeing high-quality human biomaterial. In light of diabetes-tailored biobanking, we describe our newly initiated activities and introduce the diverse technology platforms that can be used for the investigation of promising molecular targets pertinent for diabetes. With this article we demonstrate that the preservation of rare specimen is also particularly relevant in the non-neoplastic field and contributes to basic investigation, promotes comprehensive scientific data and fortifies the sustainability for diabetes research. In addition, the increased understanding of how metabolic imbalance triggers diabetes onset and progression and favors diabetic late symptoms might hold some promise for future innovative diagnostic and/ or therapeutic applications, eventually adding to the improvement of patient care.